Data on European seabass fed with methionine-enriched diets obtained through label free shotgun proteomics - Farinha, Ana Paula (2021)
This data article is associated with the research article "Evaluating the impact of methionine-enriched diets in the liver of European seabass through label-free shotgun proteomics". Here it is described the data obtained from proteomic analysis of 36 European seabass juveniles (3 fish x 3 replicate tanks) after 18 days of feeding with experimental diets containing four inclusion levels of methionine (Met): 0.77%, 1%, 1.36% and 1.66% Met (w/w). We analysed this dataset and compared it with that obtained during the long-term feeding period i.e., 85 days. Fish liver proteins were digested with trypsin and purified peptides were analysed by LC-MS/MS. Proteins were identified with at least two peptides at 0.1% Decoy false discovery rate (FDR). In this dataset, we present the analysis of the differential abundant proteins (DAP) with significant differences across treatments after 18 days of feeding (One-Way ANOVA, p < 0.05). Treatment's comparisons were also performed between the 18- and 85-days feeding trials through Two-Way ANOVA (p < 0.05). MS/MS raw data are available via ProteomeXChange with identifiers PXD019610 and 10.6019/PXD019610 (18-days dataset); and PXD019622 and 10.6019/PXD019622 (85-days dataset). This dataset corresponds to fish sampled after 18-days of experimental trial and is made available to support the study conducted in the afore-mentioned article, by performing the analysis during a short-term period of feeding. The data presented may be further used in other nutritional studies e.g., addressing hepatic changes mediated by Met.